2019
DOI: 10.30699/jambs.27.120.43
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Long-term survival of patients with esophageal cancer using parametric non-mixture cure rate models

Abstract: Background & Objective: Esophageal cancer (EC) has been identified as one of the most common cancers in the northeastern regions of Iran. In our study, parametric non-mixture cure rate model was applied to evaluate the effects of risk factors on the long-term survival of patients with EC in East Azerbaijan, Northeastern Iran. Materials & Methods: This retrospective cohort study of 127 patients with EC registered at Iran National Cancer Registry office in the period 2009-2010. These patients were followed up fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
(5 reference statements)
1
5
0
Order By: Relevance
“…This was a large multicenter study comprising of 5283 patients across several provinces in China. The latest population‐based study in China in 2009‐2011 showed that the age‐standardized 5‐year EC survival rate was 30.3%, and the 5‐year EC net survival of the population of the United States in 2010‐2014 was 20.0% [17‐19]. Findings from the present study showed that the 5‐year OS rate was 39.07% in the investigated 18 hospitals and we found that gender, marital status, occupation, family history of any cancer, tumor topographical site, differentiation status, and pathological stage were associated with the survival rate of EC.…”
Section: Discussionsupporting
confidence: 50%
“…This was a large multicenter study comprising of 5283 patients across several provinces in China. The latest population‐based study in China in 2009‐2011 showed that the age‐standardized 5‐year EC survival rate was 30.3%, and the 5‐year EC net survival of the population of the United States in 2010‐2014 was 20.0% [17‐19]. Findings from the present study showed that the 5‐year OS rate was 39.07% in the investigated 18 hospitals and we found that gender, marital status, occupation, family history of any cancer, tumor topographical site, differentiation status, and pathological stage were associated with the survival rate of EC.…”
Section: Discussionsupporting
confidence: 50%
“…Surgery, chemotherapy and radiotherapy alone or in combination are treatments for EC. However, the estimated 5-year survival rate of EC ranges from 10 to 39.7% [3][4][5][6][7]. In recent years, immunotherapy for EC has been reported [8,9], and clinical trials are also underway, providing novel strategies for improving patient's survival with EC.…”
Section: Introductionmentioning
confidence: 99%
“…(2018), and Zaeran et al. (2019). According to the PH specification for the latency part, the hazard and survival conditional functions of the random variable T$T^*$ can be written as follows, respectively: h(t|Y=1,x)=h0false(tfalse|Y=1false)expfalse(xβfalse),\begin{eqnarray} h(t|Y=1,{\bf x})&=&h_0(t|Y=1)\exp ({\bf x}^{\top }\bm{\beta }), \end{eqnarray} S(t|Y=1,x)=expexp(boldxbold-italicβ)H0(t|Y=1)=S0(t|Y=1)exp(boldxbold-italicβ).\begin{eqnarray} S(t|Y=1,{\bf x})&=&\exp {\left(-\exp ({\bf x}^{\top }\bm{\beta })H_0(t|Y=1)\right)}=S_0(t|Y=1)^{\exp ({\bf x}^{\top }\bm{\beta })}.…”
Section: Model Formulationmentioning
confidence: 97%
“…(2018), and Zaeran et al. (2019). This model is based on the assumption that the population under study is a mixture of two groups; some related works are Sy and Taylor (2000), Peng and Dear (2000), Gu et al.…”
Section: Introductionmentioning
confidence: 97%